Correlation Analysis between Ratio of C-Reactive Protein/Albumin and Severity of Dengue Hemorrhagic Fever in Children - Iskandar, Agustin; Norwahyuni, Yuyun; Aryati, Aryati; Aprilia, Andrea (Institute of Topical Disease Universitas Airlangga, 2021)
Dengue Hemorrhagic Fever (DHF) is a dengue infection which can cause shock and leads to mortality. Hypoalbuminemia is a marker of plasma leakage in DHF and correlated with severity of in fl ammatory response triggered by infection, including DHF. C-Reactive Protein (CRP) is a proin fl ammatory marker that also increases in DHF. This study aims to determine a correlation of CRP/albumin ratio with severity of DHF. Cross sectional study on pediatric patients diagnosed as DHF at Saiful Anwar Malang Hospital was done in July-December 2016. CRP levels were examined using immunoturbidimetry method, while albumin was examined by using Bromocresol Green (BCG) method. Correlation of CRP/albumin ratio with DHF severity was analyzed by using Pearson correlation test.The result showed that there were signi fi cant diff erences in CRP levels and CRP/albumin ratios in the Dengue Shock Syndrome (DSS) and non-DSS group (p = 0.002, p = 0.001, α<0.05). There was no signi fi cant diff erence in albumin level in the same group (p = 0.207, α <0.05). Positive correlation found in CRP and CRP/albumin ratio (r = 0.46, r = 0.49, α <0.01). On the contrary the negative correlation was found in albumin (r = -0.21, α <0.01). This is presumably because albumin is an acute phase protein which will decrease along with the severity of infection. In contrast, CRP will increase during the critical phase of infection. It can be concluded that the CRP/albumin ratio was positively correlated with DHF severity, as well as CRP levels, but not positively correlatedwith albumin.